Analysis of speech acts in selected military and civilian speeches of President Obasanjo / Aminu Basiru - Aminu, Basiru (2015)

(untitled)
The objectives of this study are to identify and analyse the commissives and directives that occur in Obasanjo’s selected military and civilian speeches. The study will again look at the similarities and differences between the commissives in his selected military and civilian speeches as well as the directives in his selected military and civilian speeches. This study will be of significant to Nigerian leaders and politicians because it will guide them on how to use language. It will also be of benefit to Nigerians since it will give them idea about what their leaders are up to. Likewise to General public and students of Pragmatics who are interest on political discourse. The study uses qualitative research method, the data for this study are six selected speeches of President Obasanjo, three from his military period and another three from his civilian period. This data are generated from the web sites, book and national daily newspapers. The theory apply for this study is Searle, (1976). The result shows that in the military and civilian commissives President Obasanjo performs 12 promises in the military speeches and 27 promises in his selected civilian speeches. In the military directives he performs 14 different kinds of directives namely advice, commands and warning while in the civilian directives he performs 8 different kinds of directives namely request, commands and warning. The similarities between Obasanjo’s military and civilian commissives are he performs promises in both speeches. Another similarity is that he uses first person plural pronoun we to share his responsibility, he also uses the modal auxiliary will, should and must in both military and civilian speeches to express willingness, futurity and strengthen his commitment. He also uses adverbs such as immediately, quickly, anytime in both military and civilian commissives to show his readiness. The difference in the military commissives he has not use the first iv person pronoun to represent himself unlike in the civilian where he uses first person singular pronoun i to commit himself and show his individual and personal responsibility. The similarities between Obasanjo’s military and civilian directives are in the military and civilian speeches he performs speech act of commands and warning. Another similarity between these speeches is that he uses first person plural pronoun i to show his individual responsibility, personal feelings and deep attachment to the acts he is performing. The difference between the directives in the military and civilian is that in the military directives he uses the modal auxiliary should while in the civilian directives he uses the modal must. Another important difference between the two is that the directives in the military centred on nation building, education and patriotism. The directives in the civilian centre on fighting corruption, promoting the image of the nation, drawing the attention of Nigerians to participate on nation building. Another difference is that in the military directives he performs the act of advice while in the civilian directives he performs the act of request.